2016
DOI: 10.4103/0972-2327.167713
|View full text |Cite
|
Sign up to set email alerts
|

Research in Parkinson′s disease in India: A review

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder affecting patients in large numbers throughout the world. In this article, we review all the published data on PD based on studies in Indian population. We have tried to consolidate the contribution of Indian studies in PD research. We found 95 articles, of which 92 were original research papers. This is a relatively less number, but in the last decade, there has been an increase in research on PD from this country. But most of them seem to be res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 125 publications
(125 reference statements)
0
11
0
Order By: Relevance
“…Comparisons of the elderly in Eastern and Western populations have shown that frequent consumption of dietary curcumin in India may be linked to a lower risk of Alzheimer's disease and a delay in age-related cognitive impairments than North American populations (Ganguli et al, 2000;Ng et al, 2006). Although the prevalence and incidence of PD in India are reported to be low (Bharucha et al, 1988;Das et al, 2010;Razdan et al, 1994;Surathi et al, 2016), larger multi-center studies across India are required to produce more accurate epidemiological data on PD and to establish whether turmeric consumption is linked to lower PD prevalence and incidence rates.…”
Section: Nutraceutical Approach To Pd Treatment and Preventionmentioning
confidence: 99%
“…Comparisons of the elderly in Eastern and Western populations have shown that frequent consumption of dietary curcumin in India may be linked to a lower risk of Alzheimer's disease and a delay in age-related cognitive impairments than North American populations (Ganguli et al, 2000;Ng et al, 2006). Although the prevalence and incidence of PD in India are reported to be low (Bharucha et al, 1988;Das et al, 2010;Razdan et al, 1994;Surathi et al, 2016), larger multi-center studies across India are required to produce more accurate epidemiological data on PD and to establish whether turmeric consumption is linked to lower PD prevalence and incidence rates.…”
Section: Nutraceutical Approach To Pd Treatment and Preventionmentioning
confidence: 99%
“…Remarkably, W. somnifera extracts have been documented to reverse PD-pathology, including levels of dopamine in the striatum (Manjunath and Muralidhara 2013 ), and improve locomotor defects in the Drosophila melanogaster model of PD (Manjunath and Muralidhara 2015 ). Further, reported studies in several PD models indicated that W. somnifera extracts significantly reverses the Parkinsonian phenotype (Surathi et al 2016 ). Although further studies are required to determine the protective mechanisms of W. somnifera extract against PD, this plant active constituent’s distinct antioxidant and anti-inflammatory properties likely attribute to correcting mitochondrial aberration and dopamine levels in the striatum.…”
Section: Potential Pharmacological Efficacy Of W Somnifera Against Pathophysiological Conditionsmentioning
confidence: 99%
“…With most of the caregivers being family members (known as informal caregivers), this role is usually donned by the spouses (61-70 years old in India, 75 years or older in USA), or adult children (AARP and National Alliance for Caregiving, 2020 ; Wandrekar et al, 2014 ) 2018 ). Since Parkinson’s disease is greater among men, the number of females enwrapped in the caregiving role are higher (Hirsch et al, 2016 ; Surathi et al, 2016 ). Consequently, more female than male caregivers are involved in daily care activities for the person with PD, in terms of assistive, supportive, and compensatory functions (Williams et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%